علاقة فعالیات المحادثة في مھارة الكلام لطلاب الصف ٧ في مدرسة العلوم الثانویة الإسلامیة المتكاملة میدان - Dea Dwi Atika Yuditia; Zulfahmi Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the relationship between students' Arabic speaking proficiency and their involvement in muhadatsah activities at SMP Islam Terpadu Al-Ulum Medan. The sample consists of 50 students from the eighth grade. The research design is correlational with a quantitative approach, using a questionnaire as the instrument. Descriptive analysis results show that the average Arabic speaking proficiency score is 27.86, and the average participation in muhadatsah activities is 26.88. Pearson correlation test reveals a strong positive relationship between Arabic speaking proficiency and involvement in muhadatsah, with a value of 0.772. The instrument proved to be reliable and valid. The study concludes that muhadatsah activities are effective in improving students' Arabic speaking skills. Therefore, the muhadatsah method needs to be adopted and further developed in Arabic language teaching at SMP Islam Terpadu Al-Ulum Medan.